Recent Progress in Solid Dispersion Technology - Kawakami, Kohsaku (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Amorphous solid dispersion (ASD) is a powerful formulation technology to improve oral absorption of poorly soluble drugs. Despite their being in existence for more than half a century, controlling ASD performance is still regarded as difficult because of ASD's natural non-equilibrium. However, recent significant advances in ASD knowledge and technology may enable a much broader use of ASD technology. This Special Issue, which includes 3 reviews and 6 original articles, focuses on recent progresses in ASD technology in hopes of helping to accelerate developmental studies in the pharmaceutical industry. In striving for a deep understanding of ASD non-equilibrium behavior, the Special issue also delves into and makes progress in the theory of soft-matter dynamics.